Exploration of Contemporary Fine Arts as a Media for Expressing Student Creativity - Aye, Khin Myo; Aung, Nay Lin; Koirala, Nirajan (Yayasan Adra Karima Hubbi, 2025)
In the evolving landscape of education, fine arts have emerged as a vital medium for fostering creativity among students. As students face increasing pressure in academic performance, artistic expression provides an alternative space for self-discovery and emotional expression. The role of contemporary fine arts in education, however, remains underexplored in many educational settings. This research investigates how contemporary fine arts serve as an effective platform for expressing student creativity. The primary objective of this study is to explore the potential of contemporary fine arts as a medium for enhancing student creativity, focusing on visual arts, sculpture, digital media, and installations as key areas of expression. This study employs a mixed-method approach combining qualitative case studies and quantitative surveys. A sample of 100 students from various high schools and universities participated, with data collected through interviews, focus groups, and questionnaires. The study revealed that contemporary fine arts significantly contribute to the enhancement of student creativity, with digital and interactive media being particularly influential. Students reported a higher level of engagement, emotional release, and self-confidence through artistic activities. Moreover, the integration of technology in art-making encouraged innovative thinking and expanded creative boundaries.